Better for everyone: Black descriptive representation and police traffic stops. (20th October 2022) - Christiani, Leah; Shoub, Kelsey; Baumgartner, Frank R.; Epp, Derek A.; Roach, Kevin
ABSTRACT: Racial disparities in citizen interactions with police are ubiquitous concerns in American communities. What difference does electoral representation make? We demonstrate that black descriptive representation in local government affects police activity and scrutiny in a given community. We use a new dataset comprised of over 79 municipal police departments spanning 6 states, based on tens of millions of individual-level traffic stops. In cities and towns with majority-black city councils, traffic stops are less likely to result in a search. This decline in search rates affects both white and black drivers, though the decline is larger for black drivers. Even after controlling for socioeconomic factors, segregation, and crime rates, descriptive representation still matters. A city council composed of a majority of black members is associated with important differences in policing, affecting both white and black residents.